Regulation for fintech Companies in Ecuador - Íñiguez Matute, Fabián (2021)
This paper analyses the regulations for fintech, neobanks and bigtech in Ecuador; the objective is to show the presence of these companies in the country and how their regulation is. The methodology of the study is qualitative and bibliographic documentary. As a result, it was found that in Ecuador there is no specific law for any of the three aforementioned figures, but, in practice, there are 32 fintech legally registered in the Internal Revenue System of Ecuador. In addition, more than USD 5 million dollars and thirty thousand transactions were handled during 2019, considering only those reported to the Superintendency of Banks. It should be noted that the Superintendency of Banks is in process of reforming the Organic Monetary and Financial Code (COMF) and strengthening the supervision and control of the financial system. As a conclusion, it is indicated that fintech, Neobancos and Bigtech energize the Ecuadorian economy and it is of vital importance to create regulations, for which it is recommended to take into account three axes: 1. formation and authorization; 2. operation and control; and 3. sanctions and crimes. It is recommended that these companies have an Information Security Officer (OSI), a fundamental pillar to prevent information security risks from materializing.